ANALISIS AKAD KERJA SAMA PERMODALAN DALAM PERSPEKTIF HUKUM ISLAM - Gatot Bintoro Putra Aji (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
In capital financing, cooperation is an essential component of economic activities, particularly within the Islamic economic system, which emphasizes principles of justice, partnership, and profit-sharing. This study aims to analyze the concept, legal foundation, and implementation of two main forms of capital cooperation contracts in Islamic law, namely mudharabah and musyarakah. This research employs a qualitative approach using a library research method by examining various sources such as the Qur'an, Hadith, classical fiqh literature, and relevant scientific journals. The results of the study indicate that mudharabah is a partnership between the capital owner (shahibul maal) and the entrepreneur or manager (mudharib), in which profits are shared according to a prior agreement, while losses are borne by the capital owner as long as there is no negligence on the part of the manager. Meanwhile, musyarakah is a partnership involving two or more parties who each contribute capital and share both risks and profits proportionally. Both contracts have strong legal foundations in Islamic law and reflect the principles of justice and balance in economic activities.The implementation of mudharabah and musyarakah contracts in contemporary economic practices, such as Islamic financial institutions, demonstrates that these contracts can serve as fairer alternatives to conventional interest-based financing systems. However, in practice, several challenges remain, including limited public understanding, business risks, and issues related to supervision and regulation. Therefore, enhancing public awareness and strengthening regulatory frameworks are necessary to ensure the optimal implementation of Sharia-based capital cooperation contracts.In conclusion, mudharabah and musyarakah are important instruments in the Islamic economic system, as they promote not only profit generation but also uphold values of justice, transparency, and public welfare.